Obstacles to Law Enforcement Against Trademark Infringement in E-Commerce Transactions: A Study of the Effectiveness of Law Number 20 of 2016 concerning Trademarks and Geographical Indications - Eko Bambang Rahmono; Edy Mulyanto; Desi Ratnasari (Civiliza Publishing, 2026)
This study examines the challenges of enforcing trademark law in Indonesia amid the rapid growth of e-commerce. Trademark infringement in digital transactions not only causes economic losses for brand owners but also exposes limitations in the effectiveness of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Using a normative juridical method with legislative, conceptual, and case approaches, the research analyzes primary legal materials (laws and court decisions), supported by secondary and tertiary sources. Data are analyzed qualitatively through reduction, presentation, and conclusion drawing. The findings reveal several key obstacles. First, technical barriers include limited infrastructure and inadequate digital forensic capabilities to detect and prove online violations. Second, capacity constraints arise from the insufficient understanding of law enforcement officials regarding technology-based infringement models. Third, jurisdictional complexities and cross-border trade present significant challenges, as e-commerce transactions often involve multiple legal systems, leading to conflicts of jurisdiction. The study concludes that the effectiveness of Law Number 20 of 2016 remains limited in addressing trademark protection in the digital era. To improve enforcement, it recommends strengthening derivative regulations, enhancing the technical and legal capacity of law enforcement agencies, and fostering international cooperation to address cross-border legal issues. These measures are essential to ensure more effective trademark protection in Indonesia’s evolving digital economy.